Mainstreaming Grameen banking: How rural banks combine sustainability with outreach to the poor in the Philippines - Hans Dieter Seibel; Fabrizio Felloni (Universität zu Köln, Arbeitsstelle für Entwicklungsländerforschung (AEF), 2003)
In many countries, Grameen replication has not fared well in terms of outreach and sustainability. There is no country where the Grameen Bank, reaching two million poor women in groups of five and centers of 30 in Bangladesh, has been truly replicated. In The Philippines, rural banks and NGOs-turned-rural-bank have made Grameen banking a highly profitable product with rapidly expanding outreach to the enterprising poor and ultra-poor, mostly women. How did they do it?
Keywords: 330; Informeller Finanzsektor; Ländlicher Finanzmarkt; Philippinen